Predication of nano-silica modified porous asphalt under dynamic creep by using finite element analysis - Al-Aidaros, A. Z.; Masri, K. A.; Putra Jaya, Ramadhansyah; Yaacob, H.; Norhidayah, A. H.; Mohd Warid, M. N. (IOP Science, 2021)
In areas with heavy rainfall, the conventional pavement may not be suitable due to low drainage capability. This will cause to a storm failure. To solve this, Porous asphalt (PA) is one of the innovative asphalts that can significantly overcome the issue of storm-water problem. The high air voids content characteristic of PA compares with conventional pavement in Malaysia is very suitable in managing the storm-water. However, PA suffers a few problems such as decrement of strength and tensile strength due to high air voids content which lead to permanent deformation. In order to enhance the performance of PA against the permanent deformation an additive material used to increase the strength of the PA called Nano-silica particles. Therefore, the purpose of this study is to evaluate the dynamic creep of Nano-silica modified PA by developing a finite element analysis (FEA) model. Moreover, this study the dynamic creep performance of porous asphalt with different proportion of Nano-silica particles 0%, 2% and 4% was predicted. A finite element model will be simulated by using ABAQUS 6.14 software for the PA sample in order to achieve the objectives of the study. From this study it was concluded that, the develop model was reliable use to predict the performance of PA in terms of dynamic creep and the utilizing of Nano-silica in PA mixture result changes in the rheological properties of the asphalt binder which lead to an enhancement of its performance against the permanent deformation.